Ups and Downs: Social Media Advocacy of Bipolar Disorder on World Mental Health Day - Nelson, Allister (Frontiers in Communication, 2019)
Bipolar disorder is a serious illness that claims hundreds of lives each year. In a watershed movement as the framing of bipolar shifts, the disease is gaining more awareness after the diagnosis of Mariah Carey and advocacy by opinion leaders like Stephen Fry. Social media advocacy is a powerhouse that celebrities with bipolar disorder utilize each World Mental Health Day to reduce stigma and increase awareness of bipolar type 1, which constitutes highs of mania and lows of depression, bipolar type 2, which includes lower hypomania and depressions, alongside the less severe mood swings of cyclothymia. This study collected 160 celebrities’ social media posts on Twitter that were shared on World Mental Health Day. It randomly sampled amongst the Tweets for thematic and content analysis to discover valences in positive and negative experiences of bipolar disorder and the framing of bipolar. To study effects of opinion leaders on the public, this random sample of opinion leaders was compared to a cumulative census sample of Twitter posts by the public. The public Tweets were gathered a month afterwards following the mental health hashtags #bipolar and #bipolardisorder. The findings of the study provide guidelines for opinion leaders to craft social media posts to increase positive framing of bipolar disorder via positively valenced, encouraging messages. The study lays out what messages resonate with the general public to reduce bipolar disorder stigma. This establishes a basis for further social media campaigns focused on positive, constructive messages that improve the well-being of bipolar individuals globally. The findings suggest that under Roger’s diffusion of innovation theory, opinion leaders diagnosed with bipolar disorder are effectively shifting the dialogue surrounding mental health to one of stigma reduction and acceptance. Mainly positively valenced Tweets were shared about bipolar disorder in the general public Twitter sphere a month after opinion leaders communicated support, comfort and encouragement on World Mental Health Day under Burleson’s inferable communication goal guidelines. The study suggests that consistent positive messaging about bipolar shared by opinion leaders will have a lasting positive frame shift towards mental health awareness if this trend continues.